Natural Products with BACE1 and GSK3β Inhibitory Activity - Prado, Paulo C.; Lima, Josa Alencar; Hamerski, Lidilhone; MagdalenaNascimentoRennNM (Mini Reviews in Medicinal Chemistry, 2023)
Alzheimer’s disease (AD) is a neurodegenerative, progressive, and fatal disorder characterized by marked atrophy of the cerebral cortex and loss of basal forebrain cholinergic neurons. The main pathological features of AD are related to neuronal degeneration and include extracellular deposition of amyloid beta plaques (Aβ plaques), intracellular formation of neurofibrillary tangles (NFTs), and neuroinflammation. So far, drugs used to treat AD have symptomatic and palliative pharmacological effects, disappearing with continued use due to neuron degeneration and death. Therefore, there are still problems with an effective drug for treating AD. Few approaches evaluate the action of natural products other than alkaloids on the molecular targets of β-amyloid protein (Aβ protein) and/or tau protein, which are important targets for developing neuroprotective drugs that will effectively contribute to finding a prophylactic drug for AD. This review gathers and categorizes classes of natural products, excluding alkaloids, which in silico analysis (molecular docking) and in vitro and/or in vivo assays can inhibit the BACE1 and GSK-3β enzymes involved in AD.
Keywords: Alzheimer